PENERAPAN METODE PEMBELAJARAN TUGAS TERSTRUKTUR UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI SISWA PADA KELAS XI IPS3 SMA NEGERI 3 KENDARI - Rahma, Wa Ode (Universitas Halu Oleo, 2018)
This type of research is Classroom Action Research. The data in this research are qualitative data and quantitative data obtained from the observation sheet and the test of learning result. Based on the data analysis, it can be concluded that: 1) The activity of students with the application of structured duty learning method in each cycle is indicated by the average score of student activity in cycle I of 2.7 which is included in the category enough to increase in cycle II to 3.5 which is included in either category; 2) Teacher's teaching activity by applying structured duty learning method, indicated by mean score in every cycle, where in cycle I the average score of teacher activity is 2.44 which is categorized enough and increased in cycle II to 3.55 good category; 3) Increased student learning outcomes class XI IPS3 SMA Negeri 3 Kendari from cycle I to cycle II. In the first cycle of 27 students only 15 students completed with a percentage of 56% with an average score of 67. In the second cycle has increased from 27 students there are 22 students who completed with a complete 81% with an average value of 74.7.Â